Perfekcionizem: prednost ali ovira za učenca? - Kranjec, Eva (Revija za elementarno izobraževanje, 2017)
Pefrectionism: Student's Advantage or Obstacle? The debate on the construct of perfectionism is an inevitable part of both social studies and humanities. This ubiquity, repeatedly leads researchers to study in more detail the specific dimensions of perfectionism and ways it is manifestated, which adds significant value to the treatment of perfectionism in different areas of an individual’s life. The following paper presents an overview of the theoretical concepts and the development of perfectionism, as well as the measurement instruments for its assessment. The main highlights of this article are based on the current scientific knowledge of perfectionism in children and adolescents within school context, wherein various implications of working with perfectionist students are being summarized.
Keywords: perfectionism; models of perfectionism; assessment; students